Social means of building the land In the narratives of Imam Sadiq, peace be upon him and its effects on society (Journal of the College of Basic Education, 2022)
The example of Imam al-Sadiq )) is the best of the people of his time, the most honorable of them in rank, and the most knowledgeable of them, not only in the affairs of Sharia, but in various types of knowledge, so you see that people have called him many titles, each of which reflects a radiant aspect of his blessed personality, and among his titles are the honest, the virtuous, the pure and the patient. Al-Qa’im, Al-Kafil, and Al-Manji, and he was called (the pillar of honor) ( ) and to him the Jaafari Shiites are affiliated for their belief in his Imamate ( ) and the first is the most famous of them, which became popular and spread among Muslims since the days of his life. God  since he was also called the truthful